Critical code : software producibility for defense (National Academies Press, 2010)
"Critical Code contemplates Department of Defense (DoD) needs and priorities for software research and suggests a research agenda and related actions. Building on two prior books--Summary of a Workshop on Software Intensive Systems and Uncertainty at Scale and Preliminary Observations on DoD Software Research Needs and Priorities--the present volume assesses the nature of the national investment in software research and, in particular, considers ways to revitalize the knowledge base needed to design, produce, and employ software-intensive systems for tomorrow's defense needs."--Publisher's description.